The Influence of Communication, Resources, and Bureaucratic Structure on the Implementation of LKPP Regulation Number 4 of 2021 on the Effectiveness of Guidance for Business Actors in the Procurement of Goods/Services - Rahmat Subekti; Ednawan Prihana; Indriyati Kamil (Journal of Creative Power and Ambition (JCPA), 2026)
This study is grounded in the increasing importance of effective policy implementation in government procurement, particularly in the context of digital transformation and regulatory reform under LKPP Regulation Number 4 of 2021. The research aims to analyze the influence of communication, resources, and bureaucratic structure on the effectiveness of business actor development in the procurement of goods and services (PBJ) within the Bandung City Government. A quantitative approach with a descriptive-verifiable survey method was employed, involving 37 respondents consisting of procurement officials and civil servants. Data were collected through structured questionnaires and analyzed using correlation and multiple linear regression techniques with SPSS. The findings reveal that communication, resources, and bureaucratic structure each have a positive and significant effect, both partially and simultaneously, on the effectiveness of business actor development. Effective communication enhances understanding and participation, adequate resources strengthen implementation capacity, and a well-structured bureaucracy improves coordination and accountability. The study concludes that the integration of these three factors is essential to achieving optimal policy outcomes, especially in a digital governance environment. This research contributes theoretically by reinforcing and extending policy implementation models in the context of digital public administration, and practically by providing strategic recommendations for improving procurement governance and business actor empowerment.